When the beasts spoke: the ecopoetics of Joy Harjo - Mancelos, João de (2016)
Joy Harjo is one of the most prominent Native American poets and musicians of her generation. In this paper I examine how Harjo creates a fictional world of anthropomorphism, fable, and personification, where rocks and rivers, animals and plants, voice a strong connection to the Creek history and landscape. I discuss how these natural elements can be seen as live symbols of a counter-culture. In fact, Harjo creates, reconstructs and reinterprets myths connected with the land, in order to denounce the Anglo-American abuse and exploitation of the natural resources, and to reinforce her belief in a worldwide indigenous community. Consequently, her poetry is part of an ethnic ecopoetics, with a strong universal appeal.